2021
DOI: 10.1002/jbm.b.34852
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of Annona muricata L. extract‐loaded electrospun scaffolds for localized treatment of breast cancer

Abstract: This paper presents in vitro studies of the sustained release of Annona muricata leaf extracts (AME) from hybrid electrospun fibers for breast cancer treatment.Electrospun hybrid scaffolds were fabricated from crude AME extracts, poly(lacticco-glycolic acid)/gelatin (PLGA/Ge) and pluronic F127. The physicochemical properties of the AME extract and scaffolds were studied. The antiproliferative effects of the scaffolds were also assessed on breast cancer (MCF-7 and MDA-MB-231) and non-tumorigenic breast (MCF10A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Acetogenins have been identified as one of the major bioactive compounds of A. muricata with activity on several cancer cell lines [15,16]. The ethanol extracts obtained from aerial parts from A. muricata in combination with doxorubicin showed important cytotoxic activity on 4T1 cells and other cancer cell lines [15][16][17][18][19][20][21][22]. Although there is an extensive amount of information about the cytotoxic properties of A. muricata, no information is available regarding its anti-cancer potential in specifically breast cancer using the extracts of plants collected in different periods of the year, and regarding the location of the place of recollection and its influences on their pharmacological and toxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Acetogenins have been identified as one of the major bioactive compounds of A. muricata with activity on several cancer cell lines [15,16]. The ethanol extracts obtained from aerial parts from A. muricata in combination with doxorubicin showed important cytotoxic activity on 4T1 cells and other cancer cell lines [15][16][17][18][19][20][21][22]. Although there is an extensive amount of information about the cytotoxic properties of A. muricata, no information is available regarding its anti-cancer potential in specifically breast cancer using the extracts of plants collected in different periods of the year, and regarding the location of the place of recollection and its influences on their pharmacological and toxic properties.…”
Section: Introductionmentioning
confidence: 99%
“…It is frequently treated using a trimodal approach that combines surgery, chemo, and radiotherapy. 3 , 9 …”
Section: Breast Cancermentioning
confidence: 99%
“… 39 , 66 They emphasize how effective drug encapsulation and regulated release can reduce systemic toxicity and the chance of tumor recurrence. 65 However, a complete understanding of the practical implications of the medicines is hampered by the lack of data demonstrating clinical outcomes or patient reactions following therapy. 39 In a test on mice, all mice survived the procedure and both methods and treatments were well received as the mice showed minimal weight changes.…”
Section: Plant Extract–loaded Scaffolds In Bc Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-proliferative effect of the ethyl acetate extract of AM leaf was due to a larger quantity of cytotoxicity on breast tumor tissue, which was caused by the A. muricata extract (Hadisaputri et al 2021). Incubation of MCF-7 and MDA-MB-231 cells with scaffolds, including A. muricata leaf extract, inhibited their growth (Akpan et al 2021). Kariyil et al (2021) also demonstrated the lethal effect of A. muricata seeds extract by cellular membranes lysis and S-stage arrest.…”
Section: Annona Muricatamentioning
confidence: 99%